Improving higher order thinking skills in high school biology: A systematic review - Alfian Primahesa; Sajidan Sajidan; Murni Ramli (Universitas Negeri Jakarta, 2023)
This research aims to analyze the approaches and strategies used to improve high school students' Higher Order Thinking Skills (HOTS) in Biology. The research reviewed 36 articles written by scholars from Indonesia and overseas. These articles sourced from various digital libraries of universities in Indonesia, and online databases such as Google scholar, Elsevier-Science Direct, Springer, Wiley, and Taylor & Francis Online. This review followed the PRISMA-P for systematic review protocol. All articles were further reviewed and assessments based on the research design, variables, approaches to improve student’s HOTS. Research trends in HOTS research the most widely used instructional model to improve HOTS are PBL, Inquiry learning, and Discovery learning. Based on the analysis, INSTAD (Inquiry+Student Team Achievement Division), and PBI+STAD (Problem Based Learning + Student Team Achievement Division) shows no improvement in students' HOTS. Application of other learning models such as Problem Based Learning (PBL), inquiry, discovery, Advance Organizer, POE (Predict, Observe, Explain), and BBL (Brain Based Learning) shows significant improvement on students' HOTS. Implementation of instruction using Laboratory activities, mixed methods learning and Nutriscore interactive media shows improvement on students' HOTS. From 36 articles, 2 articles indexed by SCOPUS, 15 indexed by SINTA, 8 proceedings, 9 theses, and 2 unindexed articles. Not every chapter in Biology is used in these articles. The most used chapter in the articles is ecosystem and environment followed by human physiology, fungi, protists, plantae, cell, and biotechnology. Most of the articles are using Bloom's taxonomy. Each of them used different taxonomy, which is Marzano's taxonomy and Gagne's taxonomy.